Early Recurrence of Neuroendocrine Liver Metastasis After Curative Hepatectomy: Risk Factors, Prognosis, and Treatment - Zhang, XF (2018)
BACKGROUND: Early tumor recurrence after curative resection typically indicates a poor prognosis. The objective of the current study was to investigate the risk factors, treatment, and prognosis of early recurrence of neuroendocrine tumor (NET) liver metastasis (NELM) after hepatic resection. METHODS: A total of 481 patients who underwent curative-intent resection for NELM were identified from a multi-institutional database. Data on clinicopathological characteristics, intraoperative details, and outcomes were documented. The optimal cutoff value to differentiate early and late recurrence was determined to be 3 years based on linear regression. RESULTS: With a median follow-up of 60 months, 223 (46.4%) patients developed a recurrence, including 158 (70.9%) early and 65 (29.1%) late recurrences. On multivariable analysis, pancreatic NET, primary tumor lymph node metastasis, and a microscopic positive surgical margin were independent risk factors for early intrahepatic recurrence. While recurrence patterns and treatments were comparable among patients with early and late recurrences, early recurrence was associated with worse disease-specific survival than late recurrences (10-year NELM-specific survival, 44.5 vs 75.8%, p < 0.001). Among the 34 (21.5%) patients who underwent curative treatment for early recurrence, post-recurrence disease-specific survival was better than non-curatively treated patients (10-year NELM-specific survival, 54.2 vs 26.3%, p = 0.028), yet similar to patients with late recurrences treated with curative intent (10-year NELM-specific survival, 54.2 vs 37.4%, p = 0.519). CONCLUSIONS: Early recurrence after surgery for NELM was associated with the pancreatic type, primary lymph node metastasis, and extrahepatic disease. Re-treatment with curative intent prolonged survival after recurrence, and therefore, operative intervention even for early recurrences of NELM should be considered.